2020
DOI: 10.1038/s43246-020-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial assembly of self-healing and mechanically stable hydrogels for degradation of organic dyes in water

Abstract: Mussel-inspired hydrogels have gained attention for underwater applications, including treatment of wastewater. However, they are typically limited by poor mechanical properties, short-term mechanical stability and by not being reusable. Here, we develop a mechanically stable and self-healing hydrogel with high mechanical strength for the degradation of dyes in wastewater, based on cellulose-derived co-polydopamine@Pd nanoparticles. A dynamic catechol redox system was achieved by reversible conversion between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…1,3,4,6,7 The widest 3D-supported catalyst reported recently is the palladium (Pd)-loaded cellulose-graft-polydopamine hydrogels of ∼11.2 cm 2 , wherein the interpenetrating network of the polymer trapped with Pd within the inter-hydrogel framework endowed durability, reactant access, and self-healing ability. 8 However, this formulation used expensive, toxic, and corrosive reactants such as palladium, graphene oxide, isopropylacrylamide, and acrylic acid, and the synthesis itself is timeconsuming (144 h) and involves strenuous bamboo pulp refining. 8 As illustrated in Figure S1, kinetic studies revealed a cascade of synthesis mechanisms: (i) porosity-driven chemisorption of Au + ions by the eggshell support as revealed by gradual depletion in the absorbance of ionic Au at 310 nm (Figure S1g) as confirmed by the disappearance of yellow color (Video S1), increased pH (from 2.7 to 6.5), and decreased ionic conductance of the reaction suspension overtime (Figure S1h); (ii) firm binding of Au + ions to negatively charged metal binding surface proteins with open flexible structures 40 and strong electrostatic interactive sites; 34−36 and (iii) reduction of Au + ions to AuNPs by reductive amino acids (Figure 2c), as evidenced by the advent of intense purple color within 6 h and AuNP characteristic absorbance at 535 nm (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…1,3,4,6,7 The widest 3D-supported catalyst reported recently is the palladium (Pd)-loaded cellulose-graft-polydopamine hydrogels of ∼11.2 cm 2 , wherein the interpenetrating network of the polymer trapped with Pd within the inter-hydrogel framework endowed durability, reactant access, and self-healing ability. 8 However, this formulation used expensive, toxic, and corrosive reactants such as palladium, graphene oxide, isopropylacrylamide, and acrylic acid, and the synthesis itself is timeconsuming (144 h) and involves strenuous bamboo pulp refining. 8 As illustrated in Figure S1, kinetic studies revealed a cascade of synthesis mechanisms: (i) porosity-driven chemisorption of Au + ions by the eggshell support as revealed by gradual depletion in the absorbance of ionic Au at 310 nm (Figure S1g) as confirmed by the disappearance of yellow color (Video S1), increased pH (from 2.7 to 6.5), and decreased ionic conductance of the reaction suspension overtime (Figure S1h); (ii) firm binding of Au + ions to negatively charged metal binding surface proteins with open flexible structures 40 and strong electrostatic interactive sites; 34−36 and (iii) reduction of Au + ions to AuNPs by reductive amino acids (Figure 2c), as evidenced by the advent of intense purple color within 6 h and AuNP characteristic absorbance at 535 nm (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Another type of GO/cellulose HG with high mechanical and thermal stabilities was prepared to remove contaminants from waste solution [ 161 ]. In another study, Yan et al [ 162 ] prepared a self-healing HG with great mechanical strength based on cellulose-derived co-polydopamine@Pd nanoparticles for the reduction of contaminant dye in wastewater. They attained >95% removal of both anionic and cationic dyes from wastewater through π–π interactions, hydrogen bonding, and coordination interactions without a significant decrease in the performance or integrity of the HG structure, even though the water molecules continuously weaken to van der Waals interaction to decrease the mechanical properties and stability of HG [ 163 , 164 , 165 ].…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…For example, the loose cross-links and high water content of the synthetic hydrogels make them mechanically weak and unable to perform the actual tasks [ 6 8 ]. Although significant advancements have been made in enhancing the mechanical strength by adding composite fillers or forming 3D networks, these results are still not satisfactory compared with natural materials [ 9 11 ]. Besides, in most practical applications, the dynamic conversion of hydrogels between tough and soft states, or tough and dissolve (or degradation) states is highly necessary [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the loose cross-links and high water content of the synthetic hydrogels make them mechanically weak and unable to perform the actual tasks [6][7][8]. Although significant advancements have been made in enhancing the mechanical strength by adding composite fillers or forming 3D networks, these results are still not satisfactory compared with natural materials [9][10][11].…”
mentioning
confidence: 99%